Assessment of clinical occupational dose reduction effect of a new interventional cardiology shield for radial access combined with a scatter reducing drape. Issue 5 (8th July 2015) - Gilligan, Paddy; Lynch, J.; Eder, H.; Maguire, S.; Fox, E.; Doyle, B.; Casserly, I.; McCann, H.; Foley, D.
<x xml:space="preserve">Abstract</x> Objectives To assess the occupational dose reduction effect of a new interventional cardiology shield for radial access combined with a scatter reducing drape. Background Transradial access for catheterization has been shown to increase occupational radiation dose. Current shielding techniques are primarily based on the femoral access. This article looks at the clinical occupational combined dose reduction effect of a commercially available shield and drape which is specific to access type. Methods The evaluation took place in a busy interventional cardiology laboratory, with a single plane 30 × 40 cm flat panel detector (Siemens Artis Zee, Germany). Radiation exposure to staff was measured using electronic personal dosimeters (Unfors RaysafeAB, Sweden) placed at the collar. Patient radiation exposure was assessed using screening time and dose area product per case. Both staff and patient radiation exposure were monitored for a number of case types and operators before, during, and after deployment of the new shield and drapes. Results The cardiologists' overall median collar badge reading per case reduced from 15.4 μSv per case without the shield/drape combination to 7.3 μSv per case with the shield drape combination in situ (P < 0.001). The radiographers badge reading was reduced from 4.2 μSv per case without to 2.5 μSv per case with the shield drape combination in situ (P < 0.001). There was no statistical difference in the cardiac technician's badge reading. Patient's dose area product was not significantly affected by the placement of the shield and drape combination. Conclusions The shield/drape combination can significantly reduce operator exposure in a cardiac catheterization laboratory. © 2015 Wiley Periodicals, Inc.